Mature larva of Stenichnus collaris (Müller & Kunze) (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
The mature larva of Stenichnus collaris is re-described on the basis of a shed larval skin. This is the first description of an immature Stenichnus identified by rearing to an adult beetle, and not only by collecting the larva in association with adults, as in previously published works. New data on the life history of St. collaris are provided, and possible serial homology of chaetotaxic structures across body segments is discussed. The structures of immature Nearctic St. turbatus, the only Stenichnus larva described with focus on the chaetotaxy, are compared with those of St. collaris and possible homologies are indicated.